Exogenous dopamine improves resistance to Botryosphaeria dothidea by increasing autophagy activity in pear. (April 2023) - Zhang, Zhenwu; Zhang, Ye; Wang, Yun; Fan, Jiaqi; Xie, Zhihua; Qi, Kaijie; Sun, Xun; Zhang, Shaoling
Abstract: Pear ring rot, a fungal disease caused by Botryosphaeria dothidea (B. dothidea), is one of the most damaging diseases in pear production, affecting fruit yield and causing economic losses. It is not clear whether dopamine, one of the catecholamines, has any role in pear ring rot resistance. In this study, we found that dopamine treatment of B. dothidea resulted in a significant upregulation of PbrTYDC expression compared to H2 O treatment (control) and reduced the levels of Hydrogen Peroxide (H2 O2 ) and Superoxide Anion (O2 − ), increased Peroxidase (POD), Catalase (CAT), Superoxide Dismutase (SOD) and Phenylalanine Ammonia-Lyase (PAL) activities, and induced a significant upregulation of related gene expression. Dopamine treatment promoted the oxidationreduction capacity of the AsA-GSH cycle to scavenge Reactive Oxygen Species (ROS), increased the expression of autophagy-related genes and the accumulation of autophagic structures, and enhanced autophagic activity. Silencing PbrTYDC and PbrATG8 in pear increased H2 O2 and·O2 −, decreased POD, CAT and SOD activities and reduced resistance to B. dothidea, which was restored by dopamine treatment. In conclusion, exogenous dopamine enhances resistance to B. dothidea by increasing the antioxidant capacity and autophagic activity of pears, and this study provides new insights for subsequent studies on B. dothidea as well as autophagy. Highlights: Exogenous dopamine enhances pear resistance to Botryosphaeria dothidea. Exogenous dopamine enhances pear autophagic activity under Botryosphaeria dothidea infection. Silencing PbrTYDC and PbrATG8 in pear reduced resistance to Botryosphaeria dothidea.